White Mustard (Sinapis alba L.) Oil in Biodiesel Production: A Review - Mitrović, Petar M.; Stamenković, Olivera S.; Banković-Ilić, Ivana; Djalović, Ivica G.; Nježić, Zvonko B.; Farooq, Muhammad; Siddique, Kadambot H. M.; Veljković, Vlada B. (Frontiers in Plant Science, 2020)
White mustard (Sinapis alba L.) seed oil has been used for cooking, food preservation, revitalization of body and hair, and biodiesel production, as well as a diesel fuel additive and an alternative biofuel. This review focuses on biodiesel production from white mustard seed oil as a feedstock. The review starts by outlining the botany, and cultivation of white mustard plants, seed harvest, drying, and storage, and seed oil composition and properties. This is followed by white mustard seed pretreatments (shelling, preheating, and grinding) and processing techniques for oil recovery (pressing, solvent extraction, steam distillation) from whole seeds, ground seed or kernels, and press cake. Novel technologies, such as aqueous, enzyme-assisted aqueous, supercritical CO2, and ultrasound-assisted solvent extraction, are also discussed. The main part of the review considers biodiesel production from white mustard seed oil, including fuel properties, performance and exhaust gas emissions. The economic, environmental, social, and human health risk/toxicological impacts of corn-based biodiesel production and use are also discussed.